2018
DOI: 10.18203/2349-3259.ijct20182085
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale of the effect of early nutritional therapy on frailty, functional outcomes and recovery of malnourished medical inpatients trial (EFFORT): a pragmatic, multicenter, randomized-controlled trial

Abstract: <p class="abstract"><strong>Background:</strong> Malnutrition is highly prevalent and strongly associated with clincial outcomes of medical inpatients. Still, the benefit of nutritional treatment to prevent adverse outcomes in medical inpatients at risk for malnutrition remains unproven. We describe the trial methods of the largest yet nutritional trial in medical inpatients including the rationale for key design decisions regarding the nutritional strategy, eligibility criteria, choice of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 38 publications
0
53
0
1
Order By: Relevance
“…B. zu: kürzeren Hospitalisationszeiten, weniger Komplikationen, weniger Rehospitalisationen, einer verbesserten Energie-und Proteinaufnahme inklusive weniger Gewichtsverlust und Verbesserung der Faustschlusskraft, einer Verbesserung der Lebensqualität usw. [24,[46][47][48][49][50][51][52][53][54][55].…”
Section: Ernährungskommissionunclassified
“…B. zu: kürzeren Hospitalisationszeiten, weniger Komplikationen, weniger Rehospitalisationen, einer verbesserten Energie-und Proteinaufnahme inklusive weniger Gewichtsverlust und Verbesserung der Faustschlusskraft, einer Verbesserung der Lebensqualität usw. [24,[46][47][48][49][50][51][52][53][54][55].…”
Section: Ernährungskommissionunclassified
“…First, the multicenter, randomized, placebo-controlled NOURISH trial (Nutrition effect On Unplanned ReadmIssions and Survival in Hospitalized patients) including 652 older adults affected by malnutrition found that a high-protein oral nutritional supplement containing beta-hydroxy-beta-methylbutyrate was associated with a significant reduction in 90 day mortality, with a number needed to treat (NNT) of 20 [8]. Second, the EFFORT (Effect of early nutritional support on Frailty, Functional Outcomes and Recovery of malnourished medical inpatients Trial) including 2028 medical inpatients at nutritional risk in eight Swiss hospitals showed that protocol-guided individualized nutritional support designed to achieve protein and energy targets results in significantly lower rates of severe complications (NNT = 25) and mortality (NNT = 37) compared to regular hospital food [9,10]. Moreover, functional decline was significantly lower, and quality of life as well as activities of daily living significantly improved.…”
mentioning
confidence: 99%
“…(There was no explanation regarding how the assessors were so blinded.) It was stated that there were “no interim analyses planned or made during the trial.” The protocol was published in 2018 . The trial was initially registered at ClinicalTrials.gov sometime between July 30, 2015, and August 4, 2015.…”
mentioning
confidence: 99%
“…I also noted that on the May 1, 2018, entry, the anticipated date of trial completion was December 2018. Since the protocol was also submitted after the trial was over, the only information that I had from the time that the trial was initiated regarding a possible early stopping of this RCT was the previous and persistent estimate that over 400 more patients were to be entered. (The 2500 estimate was registered in 2015.…”
mentioning
confidence: 99%
See 1 more Smart Citation